Metformin and HER2-positive breast cancer: Mechanisms and therapeutic implications - Sara S Bashraheel (17807612) (2023)
Due to the strong association between diabetes and cancer incidents, several anti-diabetic drugs, including metformin, have been examined for their anticancer activity. Metformin is a biguanide antihyperglycemic agent used as a first-line drug for type II diabetes mellitus. It exhibits anticancer activity by impacting different molecular pathways, such as AMP-inducible protein kinase (AMPK)-dependent and AMPK-independent pathways. Additionally, Metformin indirectly inhibits IGF-1R signaling, which is highly activated in breast malignancy. On the other hand, breast cancer is one of the major causes of cancer-related morbidity and mortality worldwide, where the human epidermal growth factor receptor-positive (HER2-positive) subtype is one of the most aggressive ones with a high rate of lymph node metastasis. In this review, we summarize the association between diabetes and human cancer, listing recent evidence of metformin’s anticancer activity. A special focus is dedicated to HER2-positive breast cancer with regards to the interaction between HER2 and IGF-1R. Then, we discuss combination therapy strategies of metformin and other anti-diabetic drugs in HER2-positive breast cancer. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2023.114676